Elasto-plastic analysis of plate bending using hybrid-stress finite element method - Orense, Rolando Paat (1989)
A numerical method is presented, based on the assumed-stress hybrid infinite model and the initial stress approach., for the elasto-plastic, small deflection analysis of plate bending under static loading. The use of the initial stress approach results in a set of simultaneous linear incremental equations to be solved at each loading step, with the elastic stiffness matrix remaining unchanged through-out the loading process, and the effects of plasticity are incorporated as equivalent element loads. Several example solutions are included to demonstrate the ability of this approach in elasto-plastic plate-bending problems.
Thesis (M.S.)--University of the Philippines Diliman.
Typescript.
Keywords: Plates (Engineering) -- Plastic properties; Elastoplasticity